Chimpanzees & bonobos - Elwood, Ann. (Mankato, Minn. Creative Education, 1991)
Presents facts about the physical characteristics and social behavior of the two types of chimpanzees, our closest animal relatives.
Includes index.
Keywords: Bonobo -- Juvenile literature; Pygmy chimpanzee -- Juvenile literature; Chimpanzees